The impact of earnings-announcement timing on technical analysis signal: The case of Indonesia - Dedhy Sulistiawan (Universitas Hayam Wuruk Perbanas, 2015)
This study discusses technical analysis signal and earnings-announcements timing. Technical analysis signal is used to capture price reaction around earnings announcement dates. Technical analysis is selected because it is potential for competing information as fundamental information in emerging market, especially in Indonesian stock market. The longer reporting lag will result in a tendency of bigger information leakage which makes price reaction before announcements stronger. That reaction produces a reliable technical analysis signal. By using Indonesian stock market data, the results show that (1) technical analysis signal generates bigger (lower) return for late (earlier) reporting, and (2) reporting lag positively affects the performance of technical analysis signal that emerge before annual earnings announcements. These findings indicate a tendency of bigger information leakage for companies that delay earnings announcements. It contributes to building a bridge between technical analysis and earnings-announcement timing studies.